Oxidative Stress In Patients With Carbon Monoxide Poisoning - Gülhan Kurtoğlu Çelik; Gül Pamukçu Günaydın; Bülent Demir; Mehmet Yılmaz; Teoman Ersen; Merve Ergin Tuncay; Havva Şahin Kavaklı (Ankara Medical Journal, 2021)
INTRODUCTION: Oxidative stress refers to formation of more reactive oxygen species (ROS) than that are eliminated by cellular defense mechanisms (antioxidants). The aim of this study is to determine oxidative stress developed in CO poisoning, to measure oxidant and antioxidant parameters and to study the effects of the NBO and HBO treatments on these parameters. METHODS: On admission to emergency department and at the end of 24th hour after the oxygen therapy, total oxidant status (TOS) was measured as an oxidative stress parameter, total antioxidant status (TAS), paraoxonase (PON), serum paraoxonase (SPON), arylesterase (ARES), and thiol (TTL) levels were measured as indicators of antioxidant capacity. RESULTS: TAS, TTL and ARES levels were found to be significantly lower in the patient group when compared to control group. There were no differences in both inital and 24th hour levels of oxidative stress parameters between the patients who received hyperbaric therapy and normobaric therapy. DISCUSSION AND CONCLUSION: Continuing decrease of TAS, PON, SPON, ARES, and TTL may be because the antioxidant capacity has not yet been replaced or reperfusion ischemia is caused by treatment. The results of our study support that oxidative balance turns against antioxidants in cases of CO poisoning.